Border malaria in China: knowledge and use of personal protection by minority populations and implications for malaria control: a questionnaire-based survey - Hill Nigel; Min Xia; Moore Sarah J; Jones Caroline; Zaixing Zhang; Cameron Mary M (BMC, 2008)
Abstract Background Malaria control in remote, forested areas of the Mekong region relies on personal protection from mosquito bites. Uptake of these methods may be limited by knowledge of the link between mosquitoes and malaria as well as social and economic aspects. Understanding barriers to uptake will inform malaria control programmes on targets for improvement of delivery. Methods A total 748 key respondents: health providers and village heads, from 187 villages and 25 different ethnic groups, were interviewed using structured questionnaires. Differences in use of personal protection, and knowledge of malaria between groups were analysed using chi-square; and binary logistic regression used for multivariate analysis. Results Malaria knowledge was poor with 19.4% of women and 37.5% of men linking mosquitoes with malaria, although 95.6% knew one or more methods of mosquito control. Virtually all respondents used personal protection at some time during the year; and understanding of malaria transmission was strongly associated with bednet use. Those working in forest agriculture were significantly more likely to know that mosquitoes transmit malaria but this did not translate into a significantly greater likelihood of using bednets. Furthermore, use of personal protection while woing outdoors was rare, and less than 3% of respondents knew about the insecticide impregnation of bednets. The use of bednets, synthetic repellents and mosquito coils varied between ethnic groups, but was significantly more frequent among those with higher income, more years of education and permanent housing. The reported use of repellents and coils was also more common among women despite their low knowledge of malaria transmission, and low likelihood of having heard information on malaria within the last year. Conclusion The use of personal protection must be increased, particularly among outdoor workers that have higher malaria risk. However, personal protection is widely used and widely accepted to prevent nuisance biting mosquitoes, with the major barrier to use being affordability. Therefore, social marketing campaigns aimed at women and those that work outdoors that provide highly subsidised products, especially insecticide impregnation kits for bednets and hammock nets are most likely to succeed in lowering malaria morbidity among non Han-Chinese groups in rural China.